Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/21655979.2021.1967713
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin1 promotes tumorigenesis and epithelial-mesenchymal transition of gastric cancer via the AKT/GSK3β/β-Catenin pathway

Abstract: α-Actinin1 (ACTN1), an actin cross-linking protein, is implicated in cytokinesis, cell adhesion, and cell migration. In addition, it is involved in the tumorigenesis and development of certain cancers, such as breast cancer. We explored the function of ACTN1 in gastric cancer (GC), which has largely remained unclear. High-throughput sequencing and public microarray datasets from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) revealed the upregulation of ACTN1 in gastric cancer with a poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…MYOF is expressed in both cardiac and skeletal muscle and plays a crucial role in muscle development by regulating the canonical Wnt signaling pathway 50 , 51 . Meanwhile, ACTN1 and ACTN4 are involved in actin filament bundling, cell adhesion and cell migration in non-muscle cells 52 , 53 . Apart from the AKV’s gene families, prominent NWV-specific gene families have been linked to the sense of smell, including more than 10 olfactory receptor gene families.…”
Section: Discussionmentioning
confidence: 99%
“…MYOF is expressed in both cardiac and skeletal muscle and plays a crucial role in muscle development by regulating the canonical Wnt signaling pathway 50 , 51 . Meanwhile, ACTN1 and ACTN4 are involved in actin filament bundling, cell adhesion and cell migration in non-muscle cells 52 , 53 . Apart from the AKV’s gene families, prominent NWV-specific gene families have been linked to the sense of smell, including more than 10 olfactory receptor gene families.…”
Section: Discussionmentioning
confidence: 99%
“…13 Elevated ACTN1 expression has been documented in a spectrum of cancers, including but not limited to gastric cancer, hepatocellular carcinoma, and oral squamous cell carcinoma. [14][15][16] For instance, Zhang et al demonstrated that ACTN1 over-expression in gastric cancer disrupts the cell cycle and attenuates apoptosis by modulating the AKT/GSK3b/b-catenin signaling axis. 14 In hepatocellular carcinoma, ACTN1 up-regulation has been linked to the suppression of the Hippo signaling pathway through its interaction with MOB1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that the ACTN1 regulates the epithelial-mesenchymal transition and tumorigenesis of gastric cancer via the AKT/GSK3 β/β-catenin pathway. 9 Besides, the ACTN1 is also over-expressed in hepatocellular carcinoma tissues by suppressing Hippo signaling via physical interaction with MOB1. 10 On the other hand, higher ACTN1 protein levels were significantly associated with poor prognosis in Oral Squamous Cell Carcinoma.…”
Section: Cutaneous Squamous Cell Carcinoma (Cscc) (Nmentioning
confidence: 99%